Factors limiting the spread of middle- and low-altitude fishes to the Qinghai-Tibet plateau - Li, Songtao; Gu, Haoran; Wang, Yuanfu; Wang, Zhijian (Frontiers in Marine Science, 2023)
The distribution pattern of species is determined by the environment and their adaptability to the environment. Qinghai-Tibet Plateau has become a natural laboratory for studying adaptive evolution due to its extreme environmental characteristics such as low temperature, low oxygen, high salinity and high ultraviolet radiation (UVR). Fish are sensitive to the environmental stress, so they are ideal materials for studying high-altitude adaptation of animals. Previous studies have mainly focused on the adaptability of plateau species, but the reasons why plain species cannot spread to the plateau have been ignored. In this study, stress experiments and histological experiments were used to compare the tolerance of six Barbini fishes (family: Cyprinidae) distributed at different altitudes and regions to low temperature, low oxygen, salinity and UVR. Results showed that the tolerance of fishes to high-altitude environmental stress factors was closely related to the environmental stress of their main habitats. The high-altitude fish Gymnocypris eckloni had strong tolerance to all stress factors, while the other five fishes from middle and low altitudes could not adapt to single or multiple stress factors, with significant interspecific differences. Among these factors, middle- and low-altitude fishes showed common low tolerance to UVR, suggesting that high UVR, the factor lacking at low altitude areas, plays an important role. Moreover, during the uplift of the Qinghai-Tibet Plateau, Schizothorax fish disappeared from the middle of the plateau. We speculate that this was caused by its intolerance to the increasingly extreme plateau environment, especially salinity.